Percutaneous suprapubic endoscopy for treatment of bladder tamponade - Golabek, Tomasz (Termedia Publishing House, 2013)
Suprapubic catheterisation is generally considered a safe procedure. It can, however, be associated with complications including haematuria. It is usually self-limiting and easily treated with non-surgical measures but at times formal treatment in the operating room may be required. We present an endoscopic management of bladder tamponade through a percutaneous approach in a 21-year-old man with the fibrotic defect completely occluding his posterior urethra preventing cystoscopic clot evacuation. To our knowledge, this is the first reported case of minimally invasive treatment of bladder tamponade using a suprapubic access. We believe this challenging case will serve as an aid to management of similar episodes.